TOXINOLOGY IN COLOMBIA: CONTRIBUTIONS OF PROGRAMA DE OFIDISMO/ESCORPIONISMO AND OTHER RESEARCH GROUPS - Pereañez, Jaime Andrés; Preciado, Lina María; Romero, Luz Elena (Vitae, 2020)
Background: Toxinology is a field of toxicology involved in studying toxins from animals, plants and microorganisms. In Colombia, in last thirty years, this area has been mainly studied by Programa de Ofidismo/Escorpionismo of the Universidad de Antioquia, however, some other research groups have been also contributed in our knowledge of venoms, toxin, effects and treatments. Objective: highlights the most important findings in toxinology made by Programa de Ofidismo/Escorpionismo and other research groups in Colombia. Methods: we collected and analyze119 manuscripts dealing with the history of ophidiology and toxinology in Colombia. Results: we describe some useful terms to understand the toxinology and their scopes. In addition, we build a brief history of ophidiology beginning with the period corresponding to the discovery of America, and ending with recent findings. Finally, we perform a great description of several results related to toxin isolation, characterization, antivenoms, clinical trials, new species descriptions, pretoemic and transcriptomic, among other. The nineteens was characterized by the study of snakebites, their clinic manifestations and the use of antivenoms. In addition, the ethnopharmacological studies of medicinal plants used in snakebite treatments began to be explored. The 2000s included the newly ethnopharmacology, toxin isolation, clinical trials, inhibitor studies, scorpion venom characterization and scorpion stings features. Finally, from 2010 until today, proteomic and transcriptomic gave the most important findings. Conclusions: Toxinology works in Colombia have contributed in our knowledge about endemic species, clinical manifestations of snakebites and scorpion stings, however, we invite to Colciencias and other funding agencies to have more resources in order to support more researchers in this field, since, snakebite is a public neglected disease and need more attention from governments and academic people. Finally, we still have ignorance about the venoms of some species and their possible mode of action. In addition, given the complexity of venoms, we ignore the potential use of toxins in current biomedicine. Thus, we must continue performing studies in toxinology.